Cash Waqf innovation in Islamic financial institution in Malaysia - Yunizar, Muhammad (2025)
Cash waqf is one of the contemporary instrument for Islamic Social Finance that has been introduced in Malaysia since 2007 . This study investigates the innovations and challenges in the management of cash waqf by Islamic financial institutions (IFIs) in Malaysia. Employing a thematic literature review, the research analyzes secondary data from institutional reports, academic publications, and regulatory frameworks. The findings reveal that while notable innovations—such as fintech integration, blockchainbased waqf platforms, waqf-linked sukuk, and digital crowdfunding—have been introduced, their implementation remains limited due to fragmented regulations, low public awareness, and a lack of standardized governance. The study showed that effective cash waqf management requires harmonized policies, greater financial literacy, and stronger collaboration between IFIs and waqf authorities. As a result, it proposes strategic improvements such as centralized regulatory oversight and digital transformation to enhance transparency, participation, and operational efficiency. The research concludes that revitalizing cash waqf through innovation and policy reform can significantly contribute to Malaysia’s socio-economic development, especially in education, healthcare, and poverty alleviation sectors. This study provides practical implications for policymakers, Islamic financial practitioners, and researchers seeking to optimize cash waqf as a viable tool in Islamic social finance